Repeat lumbar puncture in adults with bacterial meningitis. (May 2016) - Costerus, J.M.; Brouwer, M.C.; van der Ende, A.; van de Beek, D.
Abstract: In a prospective nationwide cohort study performed in the Netherlands from 2006 to 2014 we analysed clinical and laboratory characteristics of adults with community-acquired bacterial meningitis who underwent repeat lumbar puncture. Repeat lumbar puncture was performed in 124 of 1490 included episodes (8%), most commonly because of clinical deterioration (42%). Median cerebrospinal fluid (CSF) leucocyte count on admission was 1473 cells/mm 3 . Median CSF cell count showed a decrease of 19% when repeated within 2 days; of 84% within 3–7 days, of 93% within 8–14 days and of 98% within 15–21 days. Repeat lumbar puncture confirmed the diagnosis of meningitis in eight patients with normal initial CSF examination. Repeat CSF cultures yielded bacteria in nine patients, which led to identification of an underlying source of infection in two. We conclude that repeat lumbar puncture is performed in a small proportion of adults. Although it should not be seen as routine it can be useful in selected cases to confirm diagnosis, to exclude relapsing or persistent infection, or for therapeutic purpose in communicating hydrocephalus.